1999
DOI: 10.1002/(sici)1098-2264(199912)26:4<304::aid-gcc4>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Dominant genetic alterations in immortalization: Role for 20q gain

Abstract: Gain of 20q has been observed in many cancer types, including bladder cancers. However, the biological significance of low-copy-number 20q gain in human cancer pathogenesis has not yet been defined. We reported that immortalization of human uroepithelial cells (HUC) transformed with human papillomavirus 16 (HPV 16) E7 is associated with single-copy 20q gain (P = 2 x 10(-7)). We also observed 20q13.2 amplification in some cell lines, but only after 20 passages. Thus, we hypothesized that low-copy gain of 20q ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
(54 reference statements)
2
17
0
Order By: Relevance
“…The lack of immortalisation by these modulations alone is consistent with the observation that HPV E7-transduced NHUC immortalise only after a crisis period in which additional aberrations such as gains on chromosome 20q are acquired (Cuthill et al, 1999). A requirement for alterations of the Rb pathway has also been suggested when NHUC are immortalised by HPV E6, as in these cases p16 expression is commonly lost due to hemizygous deletion of 9p21 (Reznikoff et al, 1996).…”
Section: Discussionsupporting
confidence: 68%
“…The lack of immortalisation by these modulations alone is consistent with the observation that HPV E7-transduced NHUC immortalise only after a crisis period in which additional aberrations such as gains on chromosome 20q are acquired (Cuthill et al, 1999). A requirement for alterations of the Rb pathway has also been suggested when NHUC are immortalised by HPV E6, as in these cases p16 expression is commonly lost due to hemizygous deletion of 9p21 (Reznikoff et al, 1996).…”
Section: Discussionsupporting
confidence: 68%
“…This chromosome region is often amplified in many cancers and is believed to contain a dominant immortalising or transforming gene(s) (Tanner et al, 1994;Cuthill et al, 1999). Recent reports show that BORIS is a downstream regulator of cancer -testis genes: expression of BORIS in normal cells leads to derepression of cancer -testis genes MAGE-A1, NY-ESO-1 and others Vatolin et al, 2005).…”
mentioning
confidence: 99%
“…Aberrations of each chromosome were observed; however, the most striking were structural rearrangements and gain of chromosomes 5 a b c (Cuthill et al, 1999;Reznikoff et al, 1994;Savelieva et al, 1997) and trisomy of chromosome 20 is observed in human prostate epithelial cells immortalized with HPV16 E6 and E7. M-FISH data revealed amplification of chromosome 5 material to be a consistent event, as a result of small metacentric chromosome formation or translocation.…”
Section: Discussionmentioning
confidence: 99%